Flora Ecolexicon and Procedural Eco-Text of Processing Bali Local Culinary - Mirsa Umiyati; Agus Dharma Yoga Pratama; Daimond Tavares Rosa Suhartono (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2021)
Ecolinguistics is also related to the dimensions of the linguistic social environment. Language only lives in the human brain and in its social use by members of the language community. In this regard, changes in the linguistic and cultural environment, in addition to changes in the physical environment, clearly also change the richness of language cognitively and practically in social-verbal interactions. The aims of this study was to determine the lingual form of the Balinese eco-collection of flora and fauna in the dynamics of food culture, the structure of the procedural ecotext of flora-based local food processing in Balinese verbal recordings and to find out the social religious meaning of native food supporting ecotourism in the tourism industry. This research is descriptive qualitative in accordance with the nature of the symptoms and the objectives to be achieved. The data of this research were obtained through field work. Structured in-depth interviews, observations, and recordings are the mainstay of this research. Interviews were conducted in the context of applying the method of personal experience, namely the method (excavation) of personal experience. The results show that the value of the data in the form of verbal (treasury of the lexicon and terms as well as the text of procedures for processing and preserving local traditional foods based on the environment, then meaning becomes the focus of data analysis work. Language stores experience, knowledge, processes and products of human adaptation as ecological creatures In its interrelationship with its environment, the Balinese language embodies culture, marking the unique, cultural-lingual power of its people for centuries.